The Need for Developing Information Tourist and Recreational Resources to Promote Tourist Product Of Destinations In Uzbekistan - Iskandar Bohadirovich Sharafutdinov (Euro Asian Journal Publishing, 2024)
The development and promotion of Uzbek destinations are extremely pressing problems for the formation of a full-fledged domestic tourism market in Uzbekistan. It is necessary to constantly diagnose and analyze the factors constraining the demand for domestic tourism products. This article reveals the main aspects that impede the effective management of Uzbek destinations. The author pays special attention to the problem of using information tourism and recreational resources, which are an integral part of the development of a tourism product, and also influence the choice of consumers when choosing a region for their travel. In this regard, the purpose of this study is to substantiate the need to include information tourism and recreational resources in the processes of formation and promotion of the domestic tourism product. The main methodological approaches to the content of the concept under study are considered. Based on scientific literature research, the author’s interpretation of the category “information tourist and recreational resources” is given and its elemental composition is determined. The study of practical examples of domestic digital platforms for the implementation of comprehensive promotion of tourist destinations in Uzbekistan allows us to confirm the hypothesis posed by the author that information tourism and recreational resources are an independent, integral, and also structured category within the framework of the study of tourism resources in general.
Keywords: industry; information; tourism; recreational resources